Penerapan Maslahah Terhadap Hukum Inseminasi Buatan Dalam Perspektif Yusuf Al Qordliwi - Sapri Ali; syahrial Ahmad (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
The arrival of new innovations that change attitudes to life, shift perspectives and form norms in social life. In this regard, for a Muslim, new problems that arise due to advances in science and technology do not have to be confronted with the provisions of the texts in a confrontational manner, but must be resolved by ijtihad. Al-Qardlawi stated that among the characteristics of Islamic law is realistic. It does not ignore the reality (reality) in what is lawful and what is forbidden and also does not ignore this reality in everything it prescribes from the rules and laws for individuals, families, communities, countries and all Muslims. Islamic Shari'ah does not forbid something that is needed by humans in the reality of their lives, just as it does not allow for humans anything that harms them in the reality of their lives. Judging from the maslahah aspect, especially in terms of the shari'ah point of view, in this artificial insemination, Al-Qardlawi uses maslahah mursalah. This is based on the fact that in the case of artificial insemination in humans, there is no evidence that allows or forbids it. For this reason, Al-Qardlawi took the ijtihad method with maslahah mursalah. As for the position of maslahah when viewed in terms of the level and priority of its use, then Al-Qardlawi takes maslahah dlaruriyyah. Maslahah dlaruriyyah is allowed because the main purpose of marriage is to obtain and maintain offspring